Determinants of Dietary Supplement Consumption Among International Students in the University of Debrecen: Integrating Social Media Usage and Health Consciousness into the Theory of Planned Behavior - Abrar Ghaith; Omar Salem (Theory, Methodology, Practice)
Dietary supplements are popular globally and may be more susceptible due to specific challenges encountered abroad. This study looks at the factors affecting their consumption at the University of Debrecen using the Theory of Planned Behavior (TPB).